# Solve for c -4/7c=16

-47c=16
Multiply both sides of the equation by -74.
-74⋅(-47)⋅c=-74⋅16
Simplify both sides of the equation.
Simplify -74⋅(-47)⋅c.
Cancel the common factor of 7.
Move the leading negative in -74 into the numerator.
-74⋅(-47)⋅c=-74⋅16
Move the leading negative in -47 into the numerator.
-74⋅-47⋅c=-74⋅16
Factor 7 out of -7.
7(-1)4⋅-47⋅c=-74⋅16
Cancel the common factor.
7⋅-14⋅-47⋅c=-74⋅16
Rewrite the expression.
-14⋅-4⋅c=-74⋅16
-14⋅-4⋅c=-74⋅16
Cancel the common factor of 4.
Factor 4 out of -4.
-14⋅(4(-1))⋅c=-74⋅16
Cancel the common factor.
-14⋅(4⋅-1)⋅c=-74⋅16
Rewrite the expression.
-1⋅-1⋅c=-74⋅16
-1⋅-1⋅c=-74⋅16
Multiply.
Multiply -1 by -1.
1⋅c=-74⋅16
Multiply c by 1.
c=-74⋅16
c=-74⋅16
c=-74⋅16
Simplify -74⋅16.
Cancel the common factor of 4.
Move the leading negative in -74 into the numerator.
c=-74⋅16
Factor 4 out of 16.
c=-74⋅(4(4))
Cancel the common factor.
c=-74⋅(4⋅4)
Rewrite the expression.
c=-7⋅4
c=-7⋅4
Multiply -7 by 4.
c=-28
c=-28
c=-28
Solve for c -4/7c=16

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top